Herbal Candy Innovation from Oregano, Lemon, and Lemongrass: A School-Based Nutrition and Entrepreneurship Initiative for Health and Well-Being - Sumaling A. Daniel; Caroline B. Balaweg; Michelle L. Caasi; Anna Florina W. Pineda; Renalee V. Valenzuela (Future Science / FSH-PH Publications, 2026)
The study aims to develop and evaluate the acceptability and commercial viability of herbal candy made from oregano leaves (Origanum vulgare), lemon (citrus limon), and lemongrass (Cymbopogon citratus), and explore its integration into school-based nutrition and entrepreneurship initiatives in Nueva Vizcaya. These ingredients are recognized for their therapeutic properties, oregano for its antimicrobial and antioxidant capacity, lemon for its vitamin C content and immune support, and lemongrass for its anti-inflammatory and digestive benefits. The study used descriptive quantitative research designed. The study was conducted in the municipality of Aritao, Nueva Vizcaya consisted of residents aged 17-60 years old respondents. The data were gathered using a survey questionnaire and sensory evaluation tools. The nutritional values of the herbal candy were focused on the sugar content, calories, and vitamin compositions developed from the main ingredients such as oregano, lemon, lemongrass, and combined with the white sugar. The findings of the study are highly acceptable in terms of appearance, odor, flavor, sweetness, texture, and packaging. Most of the respondent are willing to pay the product at the price between ₱30 and ₱40, and constant buying habits mostly once or twice a week. The willingness to purchase one to two at a time, the projected total sales amounting to ₱17,320.00. The cost of ₱26.56 per pack, the selling price of ₱40.00, and a break-even point at only 31 packs. These results validate that the product is marketable and financially sustainable and thus appropriate for integration into school-based nutrition and entrepreneurship programs.